Standardization relevance of approaches and formation of unified technology transfer principles for obtaining substances from the laboratory development stage to implementation in the production site - Tarasenko, O. M.; Myhal, A. V.; Rudiuk, V. V.; Kukhtenko, O. S. (Social Pharmacy in Health Care, 2023)
Aim. To analyze and systematize approaches to scaling and transferring active pharmaceutical ingredients (APIs) from the laboratory to industrial production in accordance with the principles of Good Manufacturing Practice (GMP) in the pharmaceutical industry in Ukraine and worldwide; to determine the relevance of developing a single standardized algorithm of actions for approaches to scaling and transferring substances. Materials and methods. During the research, various methods, including a systemic approach, comparison, analogy and generalization of information about scaling and transferring APIs were used. Methods of scientific analysis were used to analyze recent publications in scientific and practical journals. Tabular and schematic tools for visual presentation of the data obtained were also applied. Results. Based on the analysis and research results, the largest global suppliers of synthetic APIs were identified, and the state of the domestic market for synthetic APIs was analyzed. The leading producer of substances of synthetic origin in Ukraine was determined. The analysis of literature, scientific data, and regulatory acts and recommendations on the requirements for transferring (implementing) new APIs to production highlighted: groups of substances by origin; GMP requirements for API production, according to their method of obtaining and stage; the main stages of the API’s life cycle, as well as the fundamental scheme of technology transfer from the laboratory development to industrial production. Approaches to the development and implementation of new products in production, as reflected in approved international documents, such as the Guideline on Good Manufacturing Practices for Active Pharmaceutical Ingredients, WHO TRS Technical Report, Annex 7, and ICH Q11, were analyzed and developed. It was determined that for the successful transfer of technologies between the sending unit (SU) and receiving unit (RU), it was necessary to have a Technology Transfer Specialist (TTS) – a SU expert responsible for organizing and coordinating the technology transfer process between SU and RU. The role and key areas of responsibility of this expert in the process of scaling up the technology for obtaining APIs from laboratory conditions to industrial production were identified. Conclusions. According to the results of the analysis, there is a lack of a clearly defined standardized algorithm for approaches to scaling and transferring technology for obtaining APIs in the pharmaceutical industry in Ukraine and worldwide. In the course of the research, the relevance of forming a single standardized algorithm for approaches to scaling and transferring substances from the laboratory to industrial production in accordance with the principles of GMP has been determined.